Induction of Systemic Resistance against Insect Herbivores in Plants by Beneficial Soil Microbes - Rashid, Md. Harun-Or; Chung, Young R. (Frontiers in Plant Science, 2017)
Soil microorganisms with growth-promoting activities in plants, including rhizobacteria and rhizofungi, can improve plant health in a variety of different ways. These beneficial microbes may confer broad-spectrum resistance to insect herbivores. Here, we provide evidence that beneficial microbes modulate plant defenses against insect herbivores. Beneficial soil microorganisms can regulate hormone signaling including the jasmonic acid, ethylene and salicylic acid pathways, thereby leading to gene expression, biosynthesis of secondary metabolites, plant defensive proteins and different enzymes and volatile compounds, that may induce defenses against leaf-chewing as well as phloem-feeding insects. In this review, we discuss how beneficial microbes trigger induced systemic resistance against insects by promoting plant growth and highlight changes in plant molecular mechanisms and biochemical profiles.